1999
DOI: 10.1080/0954412998036
|View full text |Cite
|
Sign up to set email alerts
|

The golden integral quality approach: From management of quality to quality of management

Abstract: Q uality is a subject`in fashion' : m any top m anagers are giving this matter greater im portance now ; many gur us are providing their precepts for m aking quality; many managers attend several seminars on quality looking for`cooking books' . Actually, quality is a serious and diý cult business; it has to become an integ ral part of managem ent. Too m any com panies are well behind the desired level of quality management practices. M anagers need to lear n and put into practice quality ideas. T herefore, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Lots of market survey results showed that profit is positively correlating with quality, whatever market size is. In terms of increased market share, quality is much more important especially when market expansion rate is low [69].…”
Section: Quality Improvementmentioning
confidence: 99%
“…Lots of market survey results showed that profit is positively correlating with quality, whatever market size is. In terms of increased market share, quality is much more important especially when market expansion rate is low [69].…”
Section: Quality Improvementmentioning
confidence: 99%
“…[5,6] We do not present a literature review of the problem, because it will need at least hundreds of pages to be settled, both for Confidence Intervals and for Design of Experiments; we list here only few docs in the references [1][2][3][4][5][6][12][13][14][15][16][19][20][21][22][23]29,[31][32][33][34][35][36][37][38].…”
Section: Confidence Level Is Taken As 95%? How Do You Get This Value?mentioning
confidence: 99%
“…We said that the problem of ignorance is so huge [1][2][3][4][5][6][12][13][14][15][16][19][20][21][22][23]29,[31][32][33][34][35][36][37][38][44][45][46][47][48][49][50][51][52][53][54] that a profound change of mind (metanoia, Deming) [5,6] is NEEDED.…”
Section: Another Scientific Analysis Of the Data [56]mentioning
confidence: 99%
“…In order to overcome the huge problem of ignorance [1][2][3][4][5][6][12][13][14][15][16][19][20][21][22][23]29,[31][32][33][34][35][36][37][38][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] a profound change of mind (metanoia, Deming) [5,6] is NEEDED: therefore we present the Theory for analyzing Scientifically the data and making Scientifically the ANOVA [17]. We limit ourselves to the very simple case of two factors, as in the case of the Nigerian "statisticians"; we assume that any datum yij is defined as generated by the following model, [ADDITIVE model] (for A, B factors) ij i j ij y e = µ + α + β + where µ provides the influence of the mean µ of the random variables Y ij , α i provides the influence of the factor A, β j provides the influence of the factor B [we do not consider αβ ij that provides the influence of the interaction AB (due to the factor A and the factor B)].…”
Section: The Theory For Making the Anovamentioning
confidence: 99%
See 1 more Smart Citation